Synthesis of 4-Aminopyrazol-5-ols as Edaravone Analogs and Their Antioxidant Activity - Yanina V. Burgart; Galina F. Makhaeva; Olga P. Krasnykh; Sophia S. Borisevich; Natalia A. Agafonova; Nadezhda V. Kovaleva; Natalia P. Boltneva; Elena V. Rudakova; Evgeny V. Shchegolkov; Galina A. Triandafilova; Denis A. Gazizov; Olga G. Serebryakova; et al. (Molecules, 2022)
One of the powerful antioxidants used clinically is Edaravone (EDA). We synthesized a series of new EDA analogs, 4-aminopyrazol-5-ol hydrochlorides, including polyfluoroalkyl derivatives, via the reduction of 4-hydroxyiminopyrazol-5-ones. The primary antioxidant activity of the compounds in comparison with EDA was investigated in vitro using ABTS, FRAP, and ORAC tests. In all tests, 4-Amino-3-pyrazol-5-ols were effective. The lead compound, 4-amino-3-methyl-1-phenylpyrazol-5-ol hydrochloride (APH), showed the following activities: ABTS, 0.93 TEAC; FRAP, 0.98 TE; and ORAC, 4.39 TE. APH and its NH-analog were not cytotoxic against cultured normal human fibroblasts even at 100 μM, in contrast to EDA. According to QM calculations, 4-aminopyrazolols were characterized by lower gaps, IP, and η compared to 4-hydroxyiminopyrazol-5-ones, consistent with their higher antioxidant activities in ABTS and FRAP tests, realized by the SET mechanism. The radical-scavenging action evaluated in the ORAC test occurred by the HAT mechanism through OH bond breaking in all compounds, directly dependent on the dissociation energy of the OH bond. All the studied compounds demonstrated the absence of anticholinesterase activity and moderate inhibition of CES by some 4-aminopyrazolols. Thus, the lead compound APH was found to be a good antioxidant with the potential to be developed as a novel therapeutic drug candidate in the treatment of diseases associated with oxidative stress.